2005
DOI: 10.1007/s10295-005-0245-y
|View full text |Cite
|
Sign up to set email alerts
|

Fed-batch fermentation for production of Kluyveromyces marxianusFII 510700 cultivated on a lactose-based medium

Abstract: A strain of Kluyveromyces marxianus was grown in batch culture in lactose-based media at varying initial lactose concentrations (10-60 g L(-1)) at 30 degrees C, pH 5.0, dissolved oxygen concentrations greater than 20%. Increasing the concentration of mineral salts three-fold at 40 g L(-1) and 60 g L(-1) initial lactose concentration showed only a small increase in the yield of biomass, from 0.38 g g(-1) to 0.41 g g(-1), indicating that the initial batch cultures were not significantly nutrient- (mineral salts)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 30 publications
2
19
1
1
Order By: Relevance
“…The cell yield on substrate, Y X/S , and the product yield on substrate, Y P/X , were calculated at the maximum enzyme activity point, as shown in Table 1. With regard to Y X/S , in assay 4, we obtained a result 0.35, which is agreement with the one obtained by Lukondeh et al [30] and Rech and Ayub [31] (0.4 and 0.38, respectively) when studying the β-galactosidase production in K. marxianus culture.…”
Section: Resultssupporting
confidence: 94%
“…The cell yield on substrate, Y X/S , and the product yield on substrate, Y P/X , were calculated at the maximum enzyme activity point, as shown in Table 1. With regard to Y X/S , in assay 4, we obtained a result 0.35, which is agreement with the one obtained by Lukondeh et al [30] and Rech and Ayub [31] (0.4 and 0.38, respectively) when studying the β-galactosidase production in K. marxianus culture.…”
Section: Resultssupporting
confidence: 94%
“…At the highest dilution rate of 0.2/h the productivity varied between 2.5 and 4.5 g/l/h and stabilized around 4 g/l/h towards the end of the fermentation. Other studies have reported productivity of 0.7 g/l/h by K. marxianus in continuous fermentation of whey with free cells [13], 2.9 g/l/h in fed-batch fermentation on lactose medium [9], and 1.3 g/l/in batch fermentation of cane juice [8]. Studies have been carried out using engineered flocculating S. cerevisiae on lactose medium, reporting a productivity of up to 2 g/l/h in continuous fermentations [5].…”
Section: Continuous Fermentation With Alginate-immobilized Cells Of Kmentioning
confidence: 96%
“…K. marxianus has been studied extensively for utilization of whey, e.g. : the effect of multiple substrates in ethanol fermentation from cheese whey [17], ethanol production from crude whey [19], batch fermentation [1,18], fed-batch fermentation [1,9,15], continuous fermentations [4,11,12], studies on cheese whey powder [6,[11][12][13][14], immobilization of thermotolerant yeast on delignified cellulosic materials [7], and alginate-immobilized yeast cells [2,3,10]. It has been found that, when using alginate-immobilized cells, cell flush-out is avoided and also the production of ethanol is raised compared with ethanol production from free cells [3].…”
Section: Introductionmentioning
confidence: 99%
“…Higher biomass concentration (30 g/l) was obtained by Revillion et al (2003) in K. marxianus CBS 6,556 whey fermentations after 20 h due to the high aeration rate, 3.5 vvm, which was superior to the levels studied in the present work (0.5, 1 and 1.5 vvm). In another study, Lukondeh et al (2005) achieved biomass concentrations between 4.7 and 23 g/l after 12 to 16 h of K. marxianus batch fermentation at 30°C and pH at 5.0, and demonstrated a positive correlation between lactose concentration and biomass production.…”
Section: Resultsmentioning
confidence: 99%